Blood group O protects against severe Plasmodium falciparum malaria through the mechanism of reduced rosetting. - Rowe, J; Handel, I; Thera, M; Deans, A; Lyke, K; Koné, A; Diallo, D; Raza, A; Kai, O; Marsh, K; Plowe, C; Doumbo, O; et al. (2007)
Malaria has been a major selective force on the human population, and several erythrocyte polymorphisms have evolved that confer resistance to severe malaria. Plasmodium falciparum rosetting, a parasite virulence phenotype associated with severe malaria, is reduced in blood group O erythrocytes compared with groups A, B, and AB, but the contribution of the ABO blood group system to protection against severe malaria has received little attention. We hypothesized that blood group O may confer resistance to severe falciparum malaria through the mechanism of reduced rosetting. In a matched case-control study of 567 Malian children, we found that group O was present in only 21% of severe malaria cases compared with 44-45% of uncomplicated malaria controls and healthy controls. Group O was associated with a 66% reduction in the odds of developing severe malaria compared with the non-O blood groups (odds ratio 0.34, 95% confidence interval 0.19-0.61, P < 0.0005, severe cases versus uncomplicated malaria controls). In the same sample set, P. falciparum rosetting was reduced in parasite isolates from group O children compared with isolates from the non-O blood groups (P = 0.003, Kruskal-Wallis test). Statistical analysis indicated a significant interaction between host ABO blood group and parasite rosette frequency that supports the hypothesis that the protective effect of group O operates through the mechanism of reduced P. falciparum rosetting. This work provides insights into malaria pathogenesis and suggests that the selective pressure imposed by malaria may contribute to the variable global distribution of ABO blood groups in the human population.